Compression ratio influence on combustion and emissions characteristic of hydrogen diesel dual fuel CI engine: Numerical Study. (15th June 2018) - Sharma, Priybrat; Dhar, Atul
Highlights: Hydrogen gas is port injected. Permissible maximum H2 energy share increased, with decreased compression ratio. The compression ratio of 14.5 and below is not suitable for diesel-hydrogen dual fuel operation. The compression ratio of 16.5 shows maximum possible HES is 35%, where else for CR of 19.5 maximum HES is 20%. The maximum potential hydrogen energy share at all investigated compression ratios reduce the HC, CO and soot emissions. Abstract: The effect of compression ratios variation on maximum potential hydrogen energy share in a dual fuel engine is studied by creating a numerical model for engine combustion and emission characteristics. Hydrogen is induction through the intake port, using port fuel injector (PFI). Compression ratio is varied in steps of 14.5, 16.5 and 19.5 in all the investigations. Hydrogen energy share variation ranged from 0% to 55%. The results show a clear trade-off between maximum hydrogen energy share and compression ratio. Knock limited maximum hydrogen energy share increased from 20% to 45% as compression (CR) is decreased from 19.5 to 14.5. At all compression ratios as the energy proportion of hydrogen is increased, emissions other than NOx show an apparent decline.